IDENTIFIKASI KERENTANAN EROSI TANAH BERDASARKAN PARAMETER MORFOMETRI DI SUB DAS KIKIM - Alharia Dinata (JURNAL ILMIAH BERING'S, 2020)
Soil erosion is an environmental problem that occurs in many parts of the world because it involves ecological, social and economic aspects. Kikim sub-watershed is part of the Musi river area, most of the topographic conditions are flat slopes (54.64%), steep slopes with a total percentage of 12.81%. Meanwhile, hydrological conditions have a maximum daily rainfall with a high category so that the potential for erosion and flooding is very high. The purpose of this study was to identify soil erosion vulnerability based on morphometric parameters. The research data used DEM-SRTM 30 meters and then extracted into a map of the sub-watershed and river networks to calculate morphometric parameters. The method used was the weighted sum analysis (WSA) with a GIS application approach. The DEM data excavation found 11 (eleven) sub-watersheds with an area ranging from 81.26 km2 to 220.50 km2, and the total length of the river was 2221.24 km. Based on the weighted results of the WSA method, two sub-watersheds (SB3 and SB7) had very high soil erosion vulnerability, moderate soil erosion vulnerability in SB1, SB2, SB4, SB8, SB10, and SB11. Furthermore, the low soil erosion vulnerability (SB9), and very low soil erosion vulnerability were at SB5 and SB6. The results of this study could be used for conservation zone planning to control soil erosion.